A direct proofreader–clamp interaction stabilizes the Pol III replicase in the polymerization mode. (22nd February 2013) - Jergic, Slobodan; Horan, Nicholas P; Elshenawy, Mohamed M; Mason, Claire E; Urathamakul, Thitima; Ozawa, Kiyoshi; Robinson, Andrew; Goudsmits, Joris M H; Wang, Yao; Pan, Xuefeng; Beck, Jennifer L; van Oijen, Antoine M; et al.
<x xml:space="preserve">Abstract</x> Processive DNA synthesis by the αεθ core of the Escherichia coli Pol III replicase requires it to be bound to the β2 clamp via a site in the α polymerase subunit. How the ε proofreading exonuclease subunit influences DNA synthesis by α was not previously understood. In this work, bulk assays of DNA replication were used to uncover a non‐proofreading activity of ε. Combination of mutagenesis with biophysical studies and single‐molecule leading‐strand replication assays traced this activity to a novel β‐binding site in ε that, in conjunction with the site in α, maintains a closed state of the αεθ–β2 replicase in the polymerization mode of DNA synthesis. The ε–β interaction, selected during evolution to be weak and thus suited for transient disruption to enable access of alternate polymerases and other clamp binding proteins, therefore makes an important contribution to the network of protein–protein interactions that finely tune stability of the replicase on the DNA template in its various conformational states.